SOCIOECONOMIC, DEMOGRAPHIC AND WORK PROFILE OF COMMUNITY HEALTHCARE ASSISTANTS - Mônica Motta Lino; Gabriela Marcellino de Melo Lanzoni; Gelson Luiz de Albuquerque; Mariana Cabral Schveitzer (Universidade Federal do Paraná, 2012)
This transversal and exploratory study aimed to characterize the socioeconomic, demographic and work profile of the community healthcare assistants in the city of Florianópolis in the state of Santa Catarina. 470 staff participated in the study, their details being collected by a structured, self-applied questionnaire. It was ascertained that the majority of the subjects had the following characteristics: female, Caucasian, young adult, married, Roman Catholic, educated to senior high school level, with previous work experience in commerce, both resident and born in the city, mother of one or two children, with an average per capita family income of three minimum salaries, and with five years' experience in the same healthcare team. It is concluded that it is possible to see the strengths and weaknesses of this group of workers, such that their potential may be maximized and the work processes improved, so as to continuously improve the standards of care given by the Brazilian National Health Service (Sistema Único de Saúde)